Production Of Lactic Acid From Co-Fermentation Of Vegetable Waste And Food Waste In Open Fermentation System - Hamid, Azlina Abdul (2013)
Food waste disposed in landfills has been associated as the cause of greenhouse gases, foul odour emission, toxic leacheate and vermin attraction as well as occupying of potential land area. In Malaysia, this waste amounts to 4.404 million tonnes in 2005 from total Municipal Solid Waste generated and is estimated to increase to 6.54 million tonnes in 2020. Due to the increasing number of waste generated and the negative outcomes, better ways of handling these organic wastes are currently being introduced. One of the steps is by using food wastes to produce beneficial products such as hydrogen and methane as well as lactic acid. In this study, food waste chemical composition was compared to Japanese food wastes and the food waste fractions that could produce highest yield were evaluated. The three food waste fractions namely starchy fraction (rice waste), cellulosic fraction (vegetable waste) and proteinaceous fraction (fish scrap) were compared against food waste. Food waste efficiency in terms of percent bioconversion was also analyzed. Furthermore, the duration of fermentation, temperature and initial pH for food waste fermentation were also confirmed in this research. Moreover, improvement of lactic acid production by adding certain concentrations of the most efficient waste fraction in food waste was also explored. All waste fractions and food waste were grinded separately in distilled deionized water 1:2 (v/v) to form food waste slurry (without sterilization), initial pH adjusted to pH 7 and fermented statically at 25oC.